Kontrol Kurami (Control Theory) Ve Gerçeklik Terapisi (Reality Therapy) - Kaner, Sema (Ankara Üniversitesi, 1993)
[Abstract Not Available]
The file in this item is the publisher version (published version) of the article.
Keywords: Ait Olma; Plan Yapma; Kontrol Kuramı; Sosyal Psikolojisi; İnsan Davranışları - Davraanış Psikolojisi; Psikoloji; William Glasser